Encrypted De-duplication over Distributed Cloud Server - Aditya Balaji, R; Pragadeeeshwaran, R; K. Sandhia, G (International Journal of Engineering and Technology, 2018)
The most common cloud service is Data Storage. In order to reduce the storage space, deduplication is used. Data deduplication is a process of removing redundant copies of same data. If a file which is already present in the cloud, is uploaded by the same user or different user, then it will not be uploaded again. Therefore storage required is decreased but reliability is also reduced. Data are encrypted and stored in cloud to protect the privacy of users and this introduces new challenges. The proposed system uses M3 algorithm for encryption and Chunking technique for deduplication. The results of the evaluation show that the security and reliability are increased in the proposed scheme.